EVALUATION MANAGEMENT BROILER PRODUCTION PROJECTS AT BAGHDAD PROVINCE USING MANAGEMENT CRITERIA - & Faeq, Ali; & Faeq, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research aims were to evaluate management of broiler production projects in Baghdad province via using the criteria of management, included production index and economic figure (PI and EF) that specified to those projects. in addition to criteria of economic efficiency also applied (INME) index number of management efficiency, in order to the research requirements, data were obtained based on a questionnaire prepared for this purpose, which was collected by personal interview of (60) projects of the broiler production projects from (516) projects representing 11.6% of the research community in Baghdad province in 2016. The results show that mean of PI and EF was (338). The increase in these two criteria is generally due to control of management procedures, while 48% of the sample projects according to the INME index gave values higher than 100. This reflects the effect of the high level of management efficiency on FCR and consequently on the level of production of meat broiler. The results were also shown in accordance with the economic and financial criteria used in the evaluation of meat broiler projects. All the categories of projects achieved positive returns. The research concluded that the sample projects are economically merit, with the benefit cost ratio (1.5). Also the broiler projects rely little on the permanent work represented by the number of administrators. This is confirmed by the low percentage of fixed costs, The research recommends to adoption of modern administrative, production and technical methods to manage the production of broiler projects and to encourage investment in such of these projects because of their economic efficiency and featured in the short cycle of capital.